2017
DOI: 10.2147/oajsm.s120058
|View full text |Cite
|
Sign up to set email alerts
|

Association between sensory function and hop performance and self-reported outcomes in patients with anterior cruciate ligament injury

Abstract: BackgroundIn patients with anterior cruciate ligament (ACL) deficiency (ACLD) or reconstruction (ACLR), sensory deficits are commonly assessed as knee kinesthesia using time-consuming laboratory equipment. Portable equipment such as that used for evaluation of vibration sense would be preferable. In contrast to kinesthesia, vibration sense is not well studied in these patients.Objectives1) To study the association between kinesthesia and vibration sense to investigate if one sensory measurement can replace the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Functional tests have been used to assess components of sports performance (strength, power and agility), to determine the return to sports, evaluate the effectiveness of interventions for neuromuscular training and predict LE injuries 28 . Functional tests of single-limb hops, as SHT and F8T, evaluate motor functionality of individuals because they require postural and neuromuscular control 29 , since they have lateral displacements components (SHT) 14,17 , movements that lead to rotational stress (F8T) 14,15 , in addition to require quick changes of direction and cover physical components such as coordination and speed 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Functional tests have been used to assess components of sports performance (strength, power and agility), to determine the return to sports, evaluate the effectiveness of interventions for neuromuscular training and predict LE injuries 28 . Functional tests of single-limb hops, as SHT and F8T, evaluate motor functionality of individuals because they require postural and neuromuscular control 29 , since they have lateral displacements components (SHT) 14,17 , movements that lead to rotational stress (F8T) 14,15 , in addition to require quick changes of direction and cover physical components such as coordination and speed 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…This study included 15 participants eligible from a previous cohort (data collected in 2016) 12 and 128 participants recruited between 2018 and 2022, who were all part of the longitudinal project. 15 Consequently, a total of 143 participants (n = 72 female) with a mean age of 25.0 ± 5.7 years were included ( Table 1 ). Inclusion criteria were time of approximately 1 year after ACLR (range, 8-16 months), with or without associated injuries, and age of 15 to 35 years.…”
Section: Methodsmentioning
confidence: 99%
“…In cross-sectional studies, worse hop performance and worse movement quality have been demonstrated to be weakly to moderately related to lower scores on the KOOS Sport and Recreation subscale at 2 to 3 years after ACLR, 21,49 whereas there were no associations between knee muscle strength at 3 years 21 or sensory function at 5 months 15 after ACLR and KOOS Sport and Recreation subscores. Furthermore, evidence for whether there is an association between isokinetic knee strength or hop performance and psychological readiness to RTS at 6 to 12 months after ACLR is inconsistent.…”
mentioning
confidence: 96%
“…For example, patients with ACLD exhibit poorer proprioception 17 ) and use different postural and motor control strategies compared to those with ACLR 23 , 24 ) . Poor kinesthesia has also been found related to worse self-reported function in patients with ACLD but not after ACLR 25 ) . Thus, separate analysis of patients with ACLD and ACLR may be warranted in studies on sensorimotor function after ACL injury.…”
Section: Introductionmentioning
confidence: 99%